PENGARUH VOLUME PERDAGANGAN SAHAM, CAPITAL GAIN, TINGKAT SUKU BUNGA TERHADAP INDEKS HARGA SAHAM PERUSAHAAN (Studi Empiris Pada Perusahaan Food And Beverages Yang Go Public Di Bursa Efek Indonesia) - M. SUKRON; Afifudin Afifudin; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTThis study aims to determine the effect of stock trading volume, capitalgains and interest rates on the stock price index of food and beverages companies.This research was conducted at the Indonesia stock exchange by selectingsamples of companies. Listed on the Indonesia stock exchange in 2014 to 2016. Atotal of 13 companies. variables in stock index, capital gain, interest ratestogether have a significant effect on stock trading volume. The amount ofinfluence obtained on the stock price index variable, capital gain, the interest rateon stock trading volume is 41.2%. while the remaining 58.8% are influenced byother variables outside the regression equation.Keywords : stock price index, capital gain, interest rate and stock trading volume.